Fundaments in the management of nvivo 9 as a tool for qualitative studies - Mª Ángeles Valdemoros-; Ana Ponce-; Eva Sanz-Arazuri (Universidad de La Rioja, 2013)
The purpose of this article is tohighlight the advantages of using NVIVO 9 software as a support tool for the development of research based on qualitative data analysis. Also the funtions and tasks offered and the keys to consider for use are presented. The article draws on a research on physical activity to facilitate understanding of NVIVO 9. The NVIVO 9 is a tool that enables the handling of large amounts of textual records against each other, facilitates the search and retrieval of text and encoding and allows the investigator to work with an unlimited number of categories and subcategories.